Dynamic interference coordination scheme based on the iterative joint transmission in ultra dense network - Xiaona LI; Zhongfang WANG; Qian CHENG; Jingwen FU; Shunliang ZHANG (Tongxin xuebao)
In consideration of the rapidly increasing number of cells and users in the ultra-dense network,how to realize dynamic interference coordination by selecting the appropriate joint transmission users was studied,so as to improve the spectral efficiency of the edge users.All users were classified by dynamic coordination cluster division and dynamic joint-muting transmission.The iterative optimization algorithm was used to further improve the system performance and solve the problem of selecting the number of joint transmission users.The simulation results prove that compared with the conventional CoMP JT scheme,the proposed scheme has significant performance gains in the cell edge spectral efficiency without reducing the cell average spectral efficiency.